Second thoughts about who is first: the medical triage of violent perpetrators and their victims. Issue 5 (29th August 2016) - Gold, Azgad; Strous, Rael D
Abstract : Extreme intentional and deliberate violence against innocent people, including acts of terror and school shootings, poses various ethical challenges, some related to the practice of medicine. We discuss a dilemma relating to deliberate violence, in this case the aftermath of a terror attack, in which there are multiple injured individuals, including the terror perpetrator. Normally, the priority of medical treatment is determined based on need. However, in the case of a terror attack, there is reason to question this. Should the perpetrator of extreme violence receive medical treatment on the scene before the victims if he or she is designated as the most seriously injured? Or rather, should victims receive medical care priority if they are also in some life-threatening danger, although not at the same level of severity as the perpetrator? We present two opposing approaches: the conventional 'no-exceptions' approach, which gives priority to the terrorist, and the justice-oriented 'victim first' approach, which gives priority to the victims. Invoking concepts of retributive justice, distributive justice and corrective justice, this latter approach suggests that 'value-neutrality' can lead to injustice. Perpetrators of terror-like violence should be treated as an act of humanism and good ethical medical practice. However, in clear and obvious terror-like situations, to treat the perpetrators of violence before their victims may be unjust. Thus, in some specific situations, the 'victim first' approach may be considered a legitimate alternative triage policy.